Faktor-faktor yang mempengaruhi price earnings ratio - DEWI AGUSTINA (Jurnal Bisnis dan Akuntansi, 2016)
This research was conducted to determine the factors that influence the Price Earnings Ratio on the companies listed in Indonesian Stock Exchange. These factors are Corporate Size, Debt to Asset Ratio, Dividend Payout Ratio, Earnings Growth, Debt to Equity Ratio, Return on Equity, and Profit Margin. The analysis and decision making about the hypothesis of this research are using multiple regression on panel data which meets the criteria of purposive sampling. Sample of this research is based on companies which are listed in the manufacturing sectors of Indonesian Stock Exchange. The number of qualified data used as the sample in this research is 99. The results of this research indicated the Corporate Size, Dividend Payout Ratio, Return on Equity and Profit Margin has influence on the Price Earnings Ratio, while the Debt to Asset Ratio, Earnings Growth, and Debt to Equity Ratio not influence on the Price Earnings Ratio.